Students’ Perceptions of Language Etiquette Learning in Professional Contexts: A Qualitative Study - Mutia Nasution; Sulistya Ningrum; Alika Azzahra; Azahra Aprilia (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
This study explores students’ perceptions of learning Language Etiquette in English for Professional Purposes courses in higher education. Using a qualitative descriptive approach, data were collected through semi-structured interviews, classroom observations, and students’ reflective journals from vocational college students. The findings indicate that Language Etiquette learning enhances students’ confidence, politeness, and ability to communicate appropriately in multicultural professional contexts. Role-play, case studies, and simulation activities were perceived as particularly effective; although some students struggled to apply etiquette principles in spontaneous or formal interactions. The study concludes that integrating Language Etiquette into English instruction strengthens students’ pragmatic and intercultural competence and recommends the use of more contextualized and interactive learning activities to improve practical application.   Keywords: Language etiquette, students’ perceptions, intercultural communication, qualitative study, professional English   DOI: https://zenodo.org/records/18084645